2003
DOI: 10.1152/japplphysiol.00368.2003
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen attenuates the exercise pressor reflex in female cats

Abstract: In humans, the pressor and muscle sympathetic nerve responses to static exercise are less in women than in men. The difference has been attributed to the effect of estrogen on the exercise pressor reflex. Estrogen receptors are abundant in areas of the dorsal horn receiving input from group III and IV muscle afferents, which comprise the sensory limb of the exercise pressor reflex arc. These findings prompted us to investigate the effect of estrogen on the spinal pathway of the exercise pressor reflex arc. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 26 publications
2
31
1
2
Order By: Relevance
“…The solution remained in the well throughout the experiment and the responses to the exercise pressor reflex were tested 30, 45, and 60 min after the estrogen solution had been applied. The stability of the exercise pressor reflex over this 60-min time period has been established (24,25). Similarly, estrogen has been shown to attenuate the reflex over this time period (24,25).…”
Section: Methodsmentioning
confidence: 93%
See 4 more Smart Citations
“…The solution remained in the well throughout the experiment and the responses to the exercise pressor reflex were tested 30, 45, and 60 min after the estrogen solution had been applied. The stability of the exercise pressor reflex over this 60-min time period has been established (24,25). Similarly, estrogen has been shown to attenuate the reflex over this time period (24,25).…”
Section: Methodsmentioning
confidence: 93%
“…Therefore, we choose our dosage of estrogen to be in the range of 70 times the physiological estrogen concentration in blood during peak estrus. Our previous study showed that an estradiol concentration of 0.01 g/ml was sufficient to attenuate the exercise pressor reflex in gonadally intact female cats 30 min after topical application to the cord (24). We choose the naloxone dose (1,000 g) because it was found in a previous study (11) to restore the pressor response to contraction that was attenuated by the ␦-opioid…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations